State of the Gauteng City-Region review 2011 - Everatt, David; Gotz, Graeme; Nyar, Annsilla; Phakathi, Sizwe; Wray, Chris (My University, 2011)
This 'State of the GCR' Review aims to contribute to ideas around how to build an integrated, sustainable and globally competitive city-region which provides more equal opportunities and a better quality of life for all its residents. The Review offers image- and map-rich representations of the considerable datasets and information that GCRO has collected and produced on the GCR, providing an overview of the key dynamics and trends affecting the economy, society, governance and environment of a city-region that is predicted to be the twelfth largest in the world by 2015. The State of the GCR is intended as both an information base and a platform for debate for all stakeholders in the region – government, business, academics and residents – around how to build on the region’s advantages and address its challenges, including rapid urbanisation and migration, poverty, and unequal distribution of wealth. GCRO’s 2011 State of the GCR Review was formally launched on Monday 17 October 2011. A second review, State of the GCR Review 2013, was launched in October 2013.
This report is associated with an online interactive website which provides the State of the Gauteng City Region review 2011 in full. Link to http://2011.legacy.gcro.unomena.net/
Keywords: city-region review 2011